1993
DOI: 10.1902/jop.1993.64.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Thick Free Gingival and Connective Tissue Autografts for Root Coverage

Abstract: Studies have shown partial to complete root coverage of denuded root surfaces with the use of thick free gingival autografts (FGGs) or subepithelial connective tissue autografts (CTGs). The purpose of this study was to determine which technique would result in more predictable root coverage of Miller Class I and II marginal tissue recession defects. Paired defects in 10 patients were randomly selected for treatment with either the FGG or the CTG. With stents as reference points, soft tissue recession was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
124
2
12

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 7 publications
11
124
2
12
Order By: Relevance
“…The results of the present study are comparable with the studies carried out by Ibbott et al 12 ; with mean root coverage of 55.70% at the end of 3 months. The present root coverage outcomes are not in agreement with those by Laney et al 13 and Jahnke et al 10 Root coverage of 50% and 43% respectively was achieved. The reason for marked improvement in the results may be due to the utilization of grafts of intermediate thickness in the present study as per the principles of successful grafting by Sullivan and Atkins.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The results of the present study are comparable with the studies carried out by Ibbott et al 12 ; with mean root coverage of 55.70% at the end of 3 months. The present root coverage outcomes are not in agreement with those by Laney et al 13 and Jahnke et al 10 Root coverage of 50% and 43% respectively was achieved. The reason for marked improvement in the results may be due to the utilization of grafts of intermediate thickness in the present study as per the principles of successful grafting by Sullivan and Atkins.…”
Section: Discussioncontrasting
confidence: 96%
“…They reported 100% root coverage in 2 of the 3 defects in the narrow category. Jahnke et al 10 found no correlation between the mesiodistal widths of the defect and the amount of root coverage achieved. In the present study bias in recession coverage based on the width of the defect was removed by equal distribution of patients in both groups based on the width of the defect.…”
Section: Discussionmentioning
confidence: 98%
“…On an average, 80% of root coverage was achieved by the connective tissue grafting (Raetzke, 1985). Nelson performed root coverage of areas with extreme gingival recession using sub-epithelial connective tissue grafts where he found an average 88% of root coverage (Nelson, 1987).The comparative analysis of root coverage achieved by Jahnke et al compared the use of gingival grafts and connective tissue grafts in the same patient and found that the amount of coverage and rate of complete coverage to be better with the use of connective tissue grafts (Jahnke et al, 1993). Hence, due to high success rate of connective tissue grafts, it is usually preferred over other procedures for root coverage.…”
Section: Discussionmentioning
confidence: 99%
“…However, the subepithelial connective tissue graft has been shown to provide a greater percentage root coverage than the epithelialised free gingival graft. 31 Similarly subepithelial connective tissue graft combined with a coronally advanced flap has been shown to provide better root coverage than the coronally advanced flap alone over a five year follow up period. 32 The mean root coverage achieved with guided tissue regeneration has been shown to vary between 48-94% and complete root coverage varies in between 0-75% of sites.…”
Section: Prognosismentioning
confidence: 99%